The role of Thallium-201 scintigraphy and Tc-99m pentavalent dimercaptosuccinic acid in diagnosis and grading of chondrosarcoma. Issue 125 (April 2020) - Jo, Olivia; Schlicht, Stephen; Slavin, John; Di Bella, Claudia; Pang, Grant; Powell, Gerard; Spelman, Tim; Choong, Peter FM
Highlights: Thallium scan may differentiate between enchondromas and low-grade chondrosarcomas. Thallium uptake was associated with a higher grade chondrosarcoma. DMSA (V) may be useful in distinguishing between benign and malignant tumours. The combined use of Thallium and DMSA (V) scans increases diagnostic confidence. Abstract: Purpose: Distinguishing between enchondromas and low-grade (grade 1) chondrosarcomas can be challenging. The aim of this study was to investigate the role of Thallium-201 scintigraphy and Technetium-99 m pentavalent dimercaptosuccinic acid (Tc-99 m DMSA (V)) in the diagnosis and grading of chondrosarcomas. Methods: 232 consecutive patients with pathologically proven cartilaginous tumours between the years 2000 and 2018 were evaluated. We included 197 patients (101 males and 96 females; median age 50 years; range 15–86 years) who underwent Thallium-201(n = 193) and/or Tc-99 m DMSA (V) scanning (n = 67). Increased uptake was defined as uptake greater than background. The reference standard was the histopathological assessment based on a grading system (grade 1–3). Data was analysed using multivariate modelling. Results: There were 46 patients with enchondromas and 151 with chondrosarcomas. Of those, 64 (enchondroma n = 21, chondrosarcoma n = 43) underwent both Thallium-201 and Tc-99 m DMSA (V). Thallium-201 uptake had 7.92 times greater odds of grade 1 chondrosarcomas than enchondromas. Thallium-201 uptake was significantly associated with the odds of a higher grade chondrosarcoma (grade 2–3). DMSA (V) positivity was associated with 4.75 times the odds of a chondrosarcoma diagnosis over enchondroma (p = 0.024). DMSA (V) uptake revealed no association with chondrosarcoma grading. Conclusion: Low-grade chondrosarcomas continue to pose a diagnostic dilemma. Thallium-201 scans may identify malignancy in benign appearing tumours as well as differentiate between low-grade and high-grade chondrosarcomas in said malignancies. DMSA (V) may be useful in distinguishing between benign and malignant entities as a whole.